Sintering and dimensional analysis of Cu/CNTs via a powder metallurgy route / Nor Shamimi Shaari...[et al.] - Shaari, Nor Shamimi; Ismaill, Muhammad Hussain; Jumahat, Aidah; Goodall, Russell
Recently, carbon nanotubes (CNTs) reinforced metal matrix composites (MMCs) have attracted an increasing interest, due to their promising properties such as high Young’s modulus and tensile strength. CNTs are considered to be an attractive reinforcement material for light weight and high-strength metallic matrix composites. When powder metallurgy (PM) is used to form these MMCs (such as Cu/CNTs composites), the sintering parameters are crucial in obtaining good final parts. This work attempts to investigate the effect of sintering parameters on physical properties in these MMCs. The process comprised of mixing of Cu powder with CNTs, compacting of the powder mixture to form green parts and sintering using a quartz tube furnace under argon atmosphere. In this study, four trials of heating rate were performed and evaluated before sintering process was conducted. Finally, the green body was initially heated isothermally at 100°C for 1 hour with heating rate of 1.0 °C/min and sintered at a temperature of 900°C for 2 hours with heating rate of 0.5 °C/min. The composites contained 0 to 4 vol% of pristine CNTs (PCNTs) and acid treatment CNTs (ACNTs), respectively. It was observed that as the CNTs content increased, the density of the composites was also decreased owing to low density of the CNTs. The sintered part in this present work has undergone volume shrinkage ranging from 12.41% to 17.02% and 13.36% to 19.30%, for Cu/PCNTs and Cu/ACNTs respectively. It was found that the heating rate played an important role in producing a good sintered part. A high heating rate induced large thermal stress and possibly increased the pore volume, leading to swelling. As part of the temperature sensitivity, the heating rate was useful in controlling microstructure evolution in sintering. A correlation between the volume shrinkage, density and porosity of the good sintered part was confirmed in this work.